Identification and characterization of the type 1 diabetes-related wheat storage globulin WP5212. - MacFarlane, Amanda J. (University of Ottawa (Canada), 2004)
Type 1 diabetes (T1D) affects approximately 200,000 Canadians and is increasing at a rate of about 3.0% per year. The development of autoimmune diabetes requires genetic susceptibility and is influenced by environmental agents. Diets in which wheat protein is the sole amino acid source are associated with high diabetes frequency in diabetes-prone BioBreeding (BBdp) rats and non-obese diabetic (NOD) mice, two models of spontaneous autoimmune diabetes. We hypothesized that an abnormal immune response to wheat, as indicated by circulating IgG antibodies, could be used to identify T1D-related wheat proteins. Similar methods have been used to identify the diabetes-related autoantigens. A wheat cDNA expression library was immunoscreened with pooled IgG antibodies from wheat gluten-fed diabetic BBdp rats. Initially, three clones were isolated. When the proteins were screened with sera from individual rats at varying risk of disease, antibody reactivity to clone WP5212, a wheat storage globulin, was strongest in diabetic rats. This antibody reactivity was not only associated with disease but also closely correlated with islet damage. Additional studies revealed that WP5212 antibodies were linked to diabetes in NOD mice and, remarkably, in human T1D patients. Furthermore, patients with both T1D and the wheat sensitive enteropathy, celiac disease (CD), displayed high WP5212 antibody reactivity, possibly representing a marker of the predisposition of T1D patients to develop CD. WP5212 shared homology with a number of dietary proteins and allergens, suggesting that diabetes-promoting structures could exist in other food plants and that immunomodulatory molecules could interact with the immune system by a common mechanism. WP5212 also shared homology with self proteins, which could act as a means for the initiation or promotion of autoimmunity. WP5212 is the first candidate dietary wheat protein implicated in the development of diabetes. Thus, screening a cDNA expression library provides a novel approach that permits the identification of environmental antigens involved in autoimmune diseases. The evidence suggests that WP5212 is strongly antigenic in three separate species that develop spontaneous diabetes. The molecular identity of this immune-targeted dietary wheat protein will help elucidate the pathogenic mechanisms by which wheat-related diabetes occurs.
Keywords: Chemistry, Biochemistry.